2006
DOI: 10.1088/0954-3899/32/11/019
|View full text |Cite
|
Sign up to set email alerts
|

Study on cosmic ray background rejection with a 30 m stand-alone IACT using non-parametric multivariate methods in a sub-100 GeV energy range

Abstract: During the last decade ground-based very high-energy γ-ray astronomy achieved a remarkable advancement in the development of the observational technique for the registration and study of γ-ray emission above 100 GeV. It is widely believed that the next step in its future development will be the construction of telescopes of substantially larger size than the currently used 10 m class telescopes. This can drastically improve the sensitivity of the ground-based detectors for γ rays of energy from 10 to 100 GeV. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…. This means that one of more elaborated versions of this technique [5,6,7,8,9] would definitely overwhelm our CNN result. Therefore, some image cleaning procedure is necessary before the CNN implementation; however, the one we used is not optimal for CNN quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…. This means that one of more elaborated versions of this technique [5,6,7,8,9] would definitely overwhelm our CNN result. Therefore, some image cleaning procedure is necessary before the CNN implementation; however, the one we used is not optimal for CNN quality.…”
Section: Resultsmentioning
confidence: 99%
“…A fully automatic algorithm without image cleaning demonstrated the same quality as the simplest version of the conventional technique, Hillas analysis [3]. This means that one of more elaborated versions of this technique [5,6,7,8,9] would definitely overwhelm our CNN result. Therefore, some image cleaning procedure is necessary before the CNN implementation; however, the one we used is not optimal for CNN quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However none of them demonstrated drastically improved performance as compared with the standard multi-parametric approach ("super-cuts"). Recent studies on the multivariate analysis in application to the data simulated for a 30 m telescope have shown that a realistic quality-factor for such low energy events is of about Q ≃ 3, which corresponds to the γ-ray and cosmic ray acceptance of κ γ ≃ 0.3 and κ CR ≃ 0.01, respectively (Konopelko et al 2005). This was achieved using Bayesian decision rules and a non-parametric estimate of the multi-parameter density.…”
Section: Image Shapementioning
confidence: 99%